The Role of Neighbourhood Support: The Relationship Training and Community Competitiveness - Irwan Kusumah, Adie; Erna; Kurniawan, Zuki (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Not all trainees were able to use the skills and abilities they acquired to become more competitive in entrepreneurship. This suggests that there is a discrepancy between the training provided and increased competitiveness in the community. The purpose of this research is to study and analyze how training and community competitiveness relate to each other. In addition, the research will investigate the role of neighborhood support as a moderating variable in this relationship. This research is conducted through a survey and uses moderated regression analysis (MRA) data analysis. The data were processed using the SPSS Version 27 program. This study involved a community of fish farming businesses operating under the guidance of the Technical Service Unit of the Cirebon City Freshwater Aquaculture Development Centre, with a total of 56 respondents. The results showed that neighborhood support, as a moderating variable, can strengthen the relationship between training and community competitiveness. In other words, the more training provided to the community and the stronger the neighborhood support, the more the community competitiveness will also increase.